خطاباتِ الٰہیہ کے فصاحتی اور بلاغتی پہلوEloquent and Rhetorical Aspects of Divine Addresses (Al-Qamar, 2022)
This study conducted on the Qur'an's expressional dimension aiming to show that the Qur'an is a linguistic miracle based on its precision to expression. Qur’an from beginning to end, linguistically and rhetorically, their inspiring words, way of delivering message to the people, rhythm, images, explanations with examples, and also with an intensity proves that no one on world could have able to produce or even approach, like that way because it’s a Divine Book. Yet despite this linguistic newness it also preserved the foundations of Arabic language and was eminently comprehensible to the people who heard it. Indeed, not only did they understand its concept but it acts as healer for the broken hearts due to its linguistic uniqueness and many of them unspeakably impressed by it. The newness of the Qur'an which manifested itself on the various levels of both content and style from word choice, to expression, Grammar, morphology, and rhetoric was a source of perplexity and amazement to those who heard the divine revelation. Therefore, in view of its word’s power, this article is being written on the topic of eloquence and rhetoric of divine addresses.
Keywords: Quran; Divine Addresses; Eloquence Rhetoric; Miracle